(untitled) (Journal of Bangladesh Academy of Sciences, 2016)
An investigation was made to see the effect of different concentrations (10, 20, 30 and 40 ppm) of 2, 3, 5- triiodobenzoic acid (TIBA) on leaf area index (LAI), leaf area duration (LAD), crop growth rate (CGR), relative growth rate (RGR) and net assimilation rate (NAR) of a cultivar of chickpea (Cicer arietinum L.) grown during rabi season of 2015 - 2016. Results revealed that LAI and LAD showed a positive response from flowering stage to maturity (66 - 110 DAS) due to 30 ppm TIBA application with maximum LAI and LAD occurring at the flowering stage. At 66 - 83 and 83 - 97 DAS, CGR was highest with the application of 30 ppm TIBA, while RGR was highest due to 10 ppm TIBA. Peak CGR was recorded at the time of pod setting to pod filling stage (8 - 97) and increased over control by 29.64%. Irrespective of the treatments, NAR was recorded maximum during flowering stage to pod setting (66 - 83 DAS) and thereafter decreased till maturity. At 66 - 83 and 83 - 97 DAS, maximum NAR values were recorded due to 30 ppm TIBA and the increases were 9.09 and 32.69% higher over the control, respectively. Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 199-205, 2016